Diversity and difference in childhood issues for theory and practice - Robinson, Kerry H.; Jones-Diaz, Criss (London Open University Press/McGraw-Hill Education, 2016)
This book provides an introduction to the key issues and theories around diversity and difference. The book helps early years and education professionals develop a critical disposition towards the taken-for-granted assumptions about children and childhood in relation to diversity, difference and social justice. The book focuses on policies, perceptions and practices around diversity and difference in education settings, identifying issues that are relevant to everyday practices. Using practical scenarios and based on research and experience, each chapter integrates understandings of practice through a variety of theoretical frameworks and explores strategies for the development of a more equitable pedagogy and practice.
Changing paradigms and theory in childhood education: critical perspectives on diversity and difference in childhood -- Doing feminist poststructuralist theory with childhood educators -- Constructions of childhood and the changing worlds of children -- The changing nature of families in the twenty-first century -- Indigeneity -- Critical multiculturalism: policy and practice -- Languages, identities and bi/multilingualism in childhood -- Social class and inequalities: deconstructions of poverty and disadvantage -- Gender in childhood Childhood and sexuality -- Revisiting the challenge of diversity and difference in childhoods.
Includes bibliographical references (pages 251-280) and index.
Keywords: Early childhood education -- Social aspects -- Australia -- Sydney (N.S.W.); Multicultural education -- Australia -- Sydney (N.S.W.); Cultural pluralism -- Study and teaching (Early childhood) -- Australia -- Sydney (N.S.W.)